2004
DOI: 10.1007/s11663-004-0006-8
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of As, Sb, Bi and Pb volatilization from industrial copper matte during Ar+O2 bubbling

Abstract: A kinetic study on minor elements removal during copper matte oxidation was designed under the presumptions of low FeO activity and of no fayalite slag formation. Copper matte with a mass fraction of Cu of 59 pct was mixed by Ar gas blowing during preheating. The matte was oxidized at 1523 and 1673 K by bubbling Ar ϩ O 2 gas through a submerged nozzle. The effects of melt temperature and input oxygen content on the oxidation rate of matte and the volatilization rate of minor elements in copper matte are discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
(38 reference statements)
3
19
0
Order By: Relevance
“…The same negligible influence of the temperature was reported by Alyaser and Brimacombe starting from experiments in a top blowing reactor [3]. A constant slope (x S /t) was found by Ajersch and Toguri [2], Asaki et al [5], and Sohn et al [6], during the desulfurization of mattes or copper sulphide, in the same trend that our results show up to very high conversions. …”
Section: 27supporting
confidence: 92%
See 1 more Smart Citation
“…The same negligible influence of the temperature was reported by Alyaser and Brimacombe starting from experiments in a top blowing reactor [3]. A constant slope (x S /t) was found by Ajersch and Toguri [2], Asaki et al [5], and Sohn et al [6], during the desulfurization of mattes or copper sulphide, in the same trend that our results show up to very high conversions. …”
Section: 27supporting
confidence: 92%
“…Results concerning the desulfurization of copper sulfide at laboratory scale have been previously reported, with different conclusions. This is not surprising at all, given the change in hydrodynamic conditions resulting from the devices where experiments were carried out: capillary tubes [2], top lancing [3,4], bubbling gas through a submerged nozzle [5,6], or thermobalance [7]. In general, the data were explained by accepting the control of the gas-side resistance, which has been considered consistent with the high oxygen utilization efficiency of the copper converter.…”
Section: Introductionmentioning
confidence: 98%
“…The usual method to estimate k L [36] has been applied to the penetration model. Because both u G and d b are constant, the coefficients calculated by this theory do not depend on conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Validation of the Larouche [101] investigated the removal of As through volatilization in the copper smelting processes based on the industrial operation data from personal visit to the smelters and also those reported in literatures. As shown in -oxygen enrichment [101] Sohn et al [102] investigated the kinetics of As volatilization by blowing varied oxygen and argon gas mixture into industrial copper matte at 1250 and 1400 °C in a gas tight vertical furnace tube, of which the results are shown in Figure 2.36. In can be seen that the As content in the matte phase substantially decreases with blowing time.…”
Section: Fractional Distribution Behaviours Of As and Zn During Coppementioning
confidence: 99%
“…A higher blowing temperature somewhat benefit the As volatilization, while the impact by input oxygen partial pressure appears to be rather small. [102] Acuna and Sherrington [91] investigated the As fractional distribution behaviour during smelting in Teniente Converter by applying a thermodynamical model similar to that reported by other researchers [96,103,104] . Using the developed model, they evaluated the effect of operating parameters on the As fractional distribution behaviour.…”
Section: Fractional Distribution Behaviours Of As and Zn During Coppementioning
confidence: 99%